Investigating the Feasibility of Using Concrete Containing Waste Paper Sludge Ash and Pozzolanic Materials to Repair Bridge Stub Columns - F. Delaram; Y. Mohammadi; M. R. Adlparvar (Advances in Civil Engineering)
In most cases, the bridge columns are underwater, and there is a risk of corrosion. The columns of marine structures and docks also include such problems. In addition to the problem of environmental hazards, the bridge columns may fail due to design problems or increasing needs. The use of waterproof concrete materials as a jacket can have a role in increasing the life of bridges. Studies in recent years show that some waste from paper industries can be used in the construction industry. In the present study, several concrete stub columns were built as bridge columns and retrofitted with concrete jackets containing waste paper sludge ash, silica nanoparticles, aluminium oxide nanoparticles, and acrylic resin. The variables included the geometric shape of the column (square and circular) and the type of nanoparticles used in the jackets (silica and aluminium oxide nanoparticles), and the curing environment of the columns (normal and sulfate environments). The combined use of nanomaterials and waste paper ash is the most important novelty of the present study. The axial loading test was performed on the columns, and the load-deflection diagrams were obtained. The ductility, stiffness, load-bearing capacity, and crack distribution were among the parameters that were used to compare different modes. The proposed jackets increased the carrying capacity by 10 to 38%, depending on the processing curing environment and the type of nanoparticles. The combined use of aluminium oxide nanoparticles and waste paper ash can improve compressive, tensile, and flexural strengths and increase the axial load capacity of bridge columns. The proposed concrete jacket effectively reduces the corrosion of concrete and steel reinforcement and improves the bridge’s useful life.